Transparent solar control film for window

The transparent solar light control film uses silica shell aerogel to selectively reflect sunlight based on angle, addressing visibility and load reduction challenges, providing effective sunlight control and energy savings.

JP2025001319APending Publication Date: 2025-01-08J TOPLINE LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023100834
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2025-01-08

AI Technical Summary

Technical Problem

Existing window films and technologies struggle to provide effective sunlight control that is not directionally dependent, maintain high visibility, and reduce heating and cooling loads without increasing thickness or manufacturing costs.

Method used

A transparent solar light control film for windows utilizing a silica shell aerogel with internal spaces partitioned between 5nm to 100nm, dispersed at 0.02% to 6.0% by mass, which selectively reflects sunlight based on incident angle through refractive index differences, enhancing solar radiation shielding without impairing visibility.

Benefits of technology

The film effectively blocks sunlight from various angles, maintains high visibility, and reduces heating and cooling loads by adjusting light entry based on seasonal solar altitudes, offering a cost-effective solution with improved performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001319000001_ABST
    Figure 2025001319000001_ABST
Patent Text Reader

Abstract

To provide a transparent solar control film for windows which shows a large shielding effect not only against solar light incident from above but also against solar light incident from a low position, has high visibility, is inexpensive, and has excellent light control performance unaffected by the direction of solar light.SOLUTION: A transparent solar control film for windows is a transparent solar control film for bonding to a glass substrate for windows. A solar control layer is formed on at least one surface of a substrate film that transmits solar light. In the solar control layer, aerogels with a silica shell are dispersed, the internal space of which is partitioned into a range of 5 nm to 100 nm, and the aerogels with a silica shell are dispersed in an amount of 0.02 mass% to 6.0 mass% relative to the total solid content of the solar control layer excluding the aerogels with a silica shell.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent solar radiation control film for windows. More specifically, the present invention relates to a transparent solar radiation control film for windows that has a light control function and is transparent and has high visibility, and that can block sunlight in summer when the solar altitude is high and let in sunlight in winter when the solar altitude is low. [Background technology]

[0002] In the fields of architecture and automobiles, from the viewpoint of energy saving measures, films coated with a thin film that reflects the heat ray component that blocks the transmission of sunlight entering through window glass and heat ray reflective films coated with a thin metal film have been disclosed in order to reduce the cooling load caused by solar radiation. However, these films have poor visibility and function in the same way in winter, which causes the problem of an increase in the heating load.

[0003] Furthermore, blinds and curtains that are commonly used to block sunlight have no selectivity with respect to the angle of incidence of sunlight on window glass, and uniformly block and adjust all light that enters a window at any angle.

[0004] As such, the window glass of buildings, automobiles, etc. is a major factor that determines the heating and cooling load. If a window film could be developed that could control the flow of light and heat in and out, the heating and cooling load could be significantly reduced.

[0005] Thus, in a transparent window component made of a plate- or sheet-like plastic material having a pair of parallel planes, multiple air layers made of planar slits of a certain thickness are formed in the vertical direction at regular intervals, inclined relative to the plane, and the interface between the transparent window component on the outside of the room and the air layers totally reflects sunlight entering from above at an angle greater than a certain angle from outside, blocking it from entering the room. Patent Document 1 discloses a light-control transparent window that allows almost complete visibility of the outside from inside the room, blocks sunlight in the summer, and lets in sunlight in the winter.

[0006] Patent Document 2 discloses a light-controlling transparent window component in which a transparent window component made of a plate- or sheet-like plastic material having a pair of parallel planes has multiple air layers made of slits formed in the vertical direction at regular intervals and inclined relative to the planes, and the interface between the plate-shaped transparent window component on the outside of the room and the air layers allows sunlight that enters from outside in winter at an angle equal to or smaller than a specified angle to the direction perpendicular to the planes to enter the room, and totally reflects sunlight that enters from above from outside in summer at an angle greater than the specified angle to the direction perpendicular to the planes, blocking it from entering the room.

[0007] Patent Document 3 also discloses a panel that includes a dimming component that includes at least one molded resin sheet having a convex portion on one side, an adhesive layer that is arranged on one side of the molded resin sheet, and a transparent plate member that is arranged on one side of the molded resin sheet via the adhesive layer, wherein when the refractive index of the molded resin sheet is A and the refractive index of the adhesive layer is B, the absolute value of the difference between the refractive index A and the refractive index B is 0.2 or less.

[0008] Furthermore, Patent Document 4 discloses an example of an insulating film coated with hollow microparticles with low thermal conductivity, which has an infrared shielding layer on one side of the film to provide heat insulation, and an insulating layer on the opposite side in which hollow nanoparticles made of silica shells and having an outer diameter within the range of 10 nm to 300 nm are dispersed in a transparent synthetic resin, giving the insulating layer a thermal conductivity of 2.5 W / mK or less. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent No. 5493150 [Patent Document 2] Patent No. 5656147 [Patent Document 3] JP 2020-095276 A [Patent Document 4] Patent No. 5810361 Summary of the Invention [Problem to be solved by the invention]

[0010] However, the light-control transparent window and the light-control transparent window member disclosed in Patent Document 1 are formed at an incline with respect to a plane, resulting in a large thickness. In order to reduce the thickness, multiple members are formed at regular intervals in the vertical direction at an incline with respect to the plane, but a certain degree of thickness is still required, making them difficult to use as window members. In addition, there is also a problem that visibility is reduced because incident light is totally reflected at the interface between the transparent window member and the air layer to prevent it from entering the room.

[0011] In addition, the panel disclosed in Patent Document 3 reduces the difference in refractive index between the light-control transparent window, the molded resin sheet, and the adhesive layer, reduces reflection due to refraction, and does not reduce visibility. In other words, these light-control components are structured such that inclined surfaces are formed at regular intervals with respect to a flat surface in a plate-shaped or sheet-shaped plastic material, are installed on the outside of the room, and total reflection is caused by the interface with the air layer on the inside of the room. In other words, by forming an inclined surface, it is designed to allow sunlight to enter at an angle greater than the critical angle, and the sunlight is totally reflected. Therefore, in order to create an accurate inclined surface, the thickness of the lower stage becomes much thicker than the upper stage, and although it can be used as a window component, there is a problem that it cannot be used as a window film to be attached to a window glass. In addition, if the inclined surface is increased, the thickness of the lower stage becomes thinner, but there is also a problem that it becomes technically difficult to create an even more accurate inclined surface, which increases the manufacturing cost. Furthermore, this light control method has the same effect as blinds in that it provides a large shielding effect only when the sunlight enters from above, but when the direction of the sunlight changes and the sunlight enters from a lower position, the shielding effect is significantly reduced. In other words, it provides a large shielding effect on a southern window during the day when the sun is high in the sky, but in the morning or evening when the sun is low in the sky, the sunlight enters from a lower position, so the shielding effect is greatly reduced.

[0012] Furthermore, the heat insulating film disclosed in Patent Document 4 had a problem in that with a conventional dispersion layer thickness of about several μm, it was difficult to obtain a large solar radiation shielding effect no matter how small the thermal conductivity was.

[0013] Therefore, the present invention has been made to solve such problems, and the main object of the present invention is to provide a transparent solar radiation control film for windows that exhibits a significant shading effect not only against sunlight incident from above, but also against sunlight incident from a low position, has high visibility, is inexpensive, and has excellent light control performance that is not affected by the direction of the sunlight.

[0014] By solving the above problems, it is possible to effectively block sunlight in the summer and effectively let sunlight into the room in the winter, thereby significantly reducing the heating and cooling load. [Means for solving the problem]

[0015] The present inventors have conducted extensive research to achieve the above object, and as a result have found that the above problems can be solved by a transparent solar radiation control film for windows that satisfies certain requirements, thereby completing the present invention.

[0016] That is, the transparent solar radiation control film for windows of the present invention is a transparent solar radiation control film for bonding to a window glass substrate, and is characterized in that a solar radiation control layer is formed on at least one side of a substrate film that transmits sunlight, in which silica shell aerogel is dispersed, the internal space of which is partitioned into areas of 5 nm to 100 nm, and the silica shell aerogel is dispersed at 0.02 mass % to 6.0 mass % relative to the total solid content of the solar radiation control layer excluding the silica shell aerogel. Here, "the internal space is partitioned into areas of 5 nm to 100 nm" refers to "the length, width, and height of the "cellular space" measured at 30 randomly selected points from an image taken with a transmission electron microscope (manufactured by FEI COMPANY) are each within the range of 5 nm to 100 nm."

[0017] In the transparent solar radiation control film for windows of the present invention, the average value of the average distance of the long axis, the median axis, and the short axis of the silica shell aerogel is preferably 0.2 μm to 20 μm, the silica shell aerogel is preferably dispersed in an amount of 0.2 mass % to 6.0 mass % relative to the total amount of solids in the solar radiation control layer excluding the silica shell aerogel, and the thickness of the solar radiation control layer is preferably 10 to 150 μm. In the present invention, the "average distance of the long axis, the median axis, and the short axis of the silica shell aerogel" is an index representing the size of the aerogel, and is the average value of the distance of the long axis, the median axis, and the short axis of the aerogel, which is an ellipsoid whose long axis, median axis, and short axis are all different from each other. In addition, the "average value of the average distances of the long axis, median axis, and short axis of silica-shelled aerogel" refers to the average value of the "average distances of the long axis, median axis, and short axis of silica-shelled aerogel" obtained in this manner, and specifically refers to the average value calculated from the average distances of the long axis, median axis, and short axis of aerogels randomly selected from 30 points on an image taken with a microscope (Keyence Corporation: model number VHX-2000).

[0018] The method for improving light control performance of the present invention is characterized by using the transparent solar radiation control film for windows of the present invention. Effect of the Invention

[0019] According to the present invention, it is possible to provide a transparent solar radiation control film for windows that exhibits a significant shading effect not only against sunlight incident from above but also against sunlight incident from a low position, has high visibility, is inexpensive, and has excellent light control performance that is not affected by the direction of the sunlight. [Brief description of the drawings]

[0020] [Figure 1] 1 is a cross-sectional view of a transparent solar radiation control film for windows according to one preferred embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a transparent solar radiation control film for windows according to another preferred embodiment of the present invention. [Diagram 3] Schematic diagram of sunlight passing through a silica-shelled aerogel. [Figure 4] FIG. 2 is a schematic diagram showing how sunlight passes through the transparent solar radiation control film for windows of the present invention. [Diagram 5] FIG. 1 is a schematic diagram showing the relationship between the incidence angle of sunlight and the number of collisions with a silica shell aerogel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The transparent solar radiation control film for windows of the present invention is a transparent solar radiation control film for bonding to a window glass substrate, characterized in that a solar radiation control layer is formed on at least one side of a substrate film that transmits sunlight, the solar radiation control layer having a dispersed silica shell aerogel whose internal space is partitioned into a range of 5 nm to 100 nm, and the silica shell aerogel is dispersed in an amount of 0.05 mass % to 5.0 mass % relative to the total solid content of the solar radiation control layer excluding the silica shell aerogel.

[0022] Generally, when materials such as metals or ceramics with high reflectance or absorption rates are used to block sunlight by reflecting or absorbing it, they also reflect and absorb light in the visible light wavelength range. Therefore, if metals or ceramics with high reflectance or absorption rates are used to increase blocking, they will also reflect and absorb visible light, compromising their function as window film.

[0023] Therefore, if only near-infrared light could be selectively blocked, the transparency and transmittance of visible light would not be compromised; however, this is extremely difficult to achieve with current technology.

[0024] In addition, the human visual field consists of the discrimination visual field (within approximately 5°) where visual acuity and color discrimination are performed, the effective visual field which is the area that can be instantly received using eye movement alone (within approximately 30° horizontally and 20° vertically), and the central visual field which processes high-density information including the central cavity. As long as the transparency and translucency of these areas is not impaired, visibility will not be significantly impaired.

[0025] Therefore, the inventors investigated a transparent solar radiation control film for windows with excellent solar radiation control performance that uses a substance transparent to the visible light band to adjust the amount of solar radiation blocked depending on the angle of the sunlight, allowing good transmission up, down, left and right from eye level, in other words up to about 30° from the line of sight, and blocking sunlight incident at angles greater than this, thereby effectively blocking summer sunlight and effectively letting winter sunlight into the room, thereby significantly reducing the heating and cooling load. This invention was arrived at.

[0026] Regarding reflection from transparent bodies, methods of reflecting solar radiation that utilize the reflective performance of the material, i.e., specular reflection, and methods of reflecting solar radiation that utilize total reflection caused by the difference in refractive index at the interface of a transparent body, as in the above-mentioned documents 1 to 3, have been disclosed.

[0027] When light enters a medium with a larger refractive index from one with a smaller refractive index at an angle of incidence equal to or greater than the critical angle, the light cannot pass through the boundary surface, and total reflection occurs.

[0028] Normally, sunlight passes through the air, then passes through and reflects off of glass panels before entering a room. Considering a transparent glass panel with a light transmittance of about 90%, the refractive index of a transparent glass panel is generally about 1.5, and can be expressed as follows according to Snell's law: Incidence from outside air to glass plate n1Sinθ1=n2Sinθ2 Radiation entering and exiting the room from the glass plate n2Sinθ2=n1Sinθ1 Medium 1 (air) Refractive index n1: 1.0 Medium 2 (glass plate) Refractive index n2: 1.5 When sunlight enters a glass plate at an angle of 60°, it refracts through the glass at an angle of 35.3° and exits the room at an angle of 60°. In other words, when the sun's altitude is 60°, it passes through the glass plate and enters the room at an angle of 60°.

[0029] And the critical angle when the light enters the room from the glass plate is Sinθ m=n1 / n2=1 / 1.5, which is 41.8°. The critical angle is a phenomenon that occurs when the exit angle is 90. Therefore, normally, sunlight enters at 60° and exits the room at an angle of 35.3° inside a glass plate with a refractive index of 1.5, so total reflection does not occur.

[0030] In the documents 1 to 3, in order to achieve total reflection, the indoor side of the acrylic plate that serves as the partition is inclined downward to the right, and X° is designed so that 35.3°+X°≧41.8°, and total reflection is achieved. However, in these methods, the thickness of the lower section is significantly thicker than that of the upper section in order to create a downward-sloping surface, and although it can be used as a window component, it cannot be used as a window film. In addition, if the number of inclined surfaces is increased, the thickness of the lower section becomes thinner, but it becomes more difficult to create an accurate inclined surface, and a problem occurs in that the manufacturing cost increases. In addition, with this method, on the south side in summer, a large shielding effect is shown during the day when the sun's altitude is high, but in the morning and evening when the sun's altitude is low, the solar rays enter from a low position, so the shielding effect is reduced. The present inventors have developed a transparent solar radiation control film for windows that has solar radiation control performance with a non-directional solar radiation shielding effect by using a method that uses reflection that occurs in a transparent body different from the above-mentioned method, that is, reflection according to the Fresnel formula.

[0031] According to Fresnel's law, when light enters the interface between materials with different refractive indices, some of it is reflected and some is transmitted. The speed at which light travels varies depending on the type of medium. When waves travel from one medium to another, the direction they travel in also changes as their speed of travel changes. The change in direction of travel at the boundary between two media is called refraction. The refractive index is the speed of light in a vacuum divided by the speed of light in a material. Light refracts between two media, and the value that indicates the ratio of the degree of refraction is called the refractive index, which is measured when light enters a medium from a vacuum state and expressed as a ratio to the vacuum. The refractive index also varies depending on the wavelength, even for the same material. This property is called dispersion.

[0032] Next, Fresnel's equation is given below. R = [(n1-n2) / (n1+n2)] 2 R: reflectance n1: refractive index of medium 1 n2: refractive index of medium 2 I=I0[1-(n1-n2) / (n1+n2)] 2 I0: Intensity of incident light I: Intensity of outgoing light

[0033] As is clear from the above, the greater the difference between the refractive index n1 of medium 1 and the refractive index n2 of medium 2, the greater the reflectance and the less light is transmitted. For example, when sunlight passes through the outside air and then a 3mm thick glass plate and enters a room, it is well known that about 4% is reflected at the surface of the glass plate, which has a refractive index of about 1.5, and about 3.8% is reflected when it leaves the glass plate into the air, resulting in a total of 7.8% transmittance of about 90%. The refractive index of air is 1.000292 at 0°C and 1 atmosphere. It is almost the same as a vacuum. Therefore, from Fresnel's equation, it can be seen that in order to increase the reflectance, a substance with a refractive index greater than that of air should be used.

[0034] In addition, the following formula shows that in order to increase the reflectance and decrease the transmittance according to the Fresnel law, it is sufficient to stack air layers and media in multiple layers. For example, when four layers are stacked, I=I0[1-{(n1-n2) / (n1+n2)} 2 ] 4 For example, aerogel with a hollow silica shell has a structure in which air is surrounded by a silica shell. Its cross section is structured in the order of silica shell, air, and silica shell.

[0035] In particular, porous aerogel, which has a network structure of nano-order fine silica particles connected together, has an internal space divided into areas of 5nm to 100nm in size, so reflection and transmission occur repeatedly. In other words, it is an ideal material for increasing reflectance according to the Fresnel equation.

[0036] Generally, when light enters a transparent material in which fine particles are dispersed, if the wavelength of the light is shorter than the size of the fine particles, it is blocked by the fine particles. However, if the wavelength is longer than the size of the fine particles, it will slip through the gap between the objects due to the diffraction phenomenon. For example, when a UV-blocking agent in which fine particles with a very small particle diameter are dispersed is irradiated with light, the strong straight-line ultraviolet rays collide with the fine particles and are blocked, but the visible light rays, which have a gentle straight-line tendency, are deflected by the diffraction phenomenon and appear transparent. However, when the particle diameter of the fine particles becomes larger than the visible light, even if the light bends a little, it cannot get around the back of the large fine particles, so the visible light is blocked as well as the ultraviolet rays. A similar phenomenon, namely diffraction, occurs with all waves, including sound waves, water waves, and electromagnetic waves (visible light, X-rays, etc.), and it can be seen that to block the sun's rays, fine particles larger than the wavelength of the sun's rays should be used.

[0037] Normally, objects such as metals absorb part of the radiant heat and reflect the rest, so the following relationship between absorptance α and reflectance ρ, "α+ρ=1," holds, and it is clear that they do not transmit in the visible light and infrared bands. However, objects such as glass and plastics are gray bodies that absorb some of the radiant heat, reflect some of it, and transmit some of it. In the case of such gray bodies, the following relationship between absorptance α, reflectance ρ, and transmittance τ holds, "α+ρ+τ=1," and it is clear that they transmit in the visible light and infrared bands. In addition, according to the Beer-Lambert law below, it can be seen that the transmittance increases if the thickness of the shell is made thinner. Absorbance A=-logT=εCL (A: absorbance, T: transmittance, ε: extinction coefficient, which is a value specific to the substance, C: molar concentration of the substance in the cell solution, L: cell length (length in the direction of irradiation))

[0038] Therefore, if transparent hollow particles with a very thin shell are used instead of solid particles with high reflection and absorption, the sunlight that penetrates the shell and enters the inside of the hollow particles will be reflected due to the difference in refractive index between the shell and the air layer inside, in addition to reflection on the surface of the hollow particles, so a transparent aerogel with a large shielding effect against sunlight can be obtained. In particular, porous aerogels with an internal space divided into 5nm to 100nm ranges can provide a large shielding effect because they repeatedly reflect and transmit sunlight.

[0039] In addition, the visibility of the solar radiation control film is such that for light in the effective visual field within 30° horizontally and 20° vertically, the transparent solar radiation control adhesive layer is thin and the distance the light travels is short, so the proportion of light that collides with the aerogel dispersed almost uniformly inside is small, and the decrease in visible light transmittance is small. Therefore, transparency and transmittance are not impaired, and visibility is almost the same as that of original glass.

[0040] In addition, since the sun's altitude in winter (from the autumnal equinox to the vernal equinox) is low and is generally within 45°, light that passes through the adhesive layer in which the aerogel is dispersed almost uniformly within a vertical angle of approximately 45° similarly has a short distance to travel and therefore is less likely to collide with the aerogel, and the solar radiation shading effect is also reduced, allowing more sunlight to enter the room.

[0041] On the other hand, in summer (from the vernal equinox to the autumn equinox), the altitude of the sun is high, at approximately 60° or more, and the distance that the light travels through the transparent solar radiation control adhesive layer in which the aerogel is uniformly dispersed increases. This increases the proportion of light that collides with the aerogel uniformly dispersed inside, and the shielding effect also increases.

[0042] In addition, in the transparent solar radiation control film of the present invention, if the incident angle is 60° or more not only in the vertical direction depending on the height of the sun's altitude but also in the horizontal direction, the distance that the light passes through the transparent solar radiation control adhesive layer becomes longer and the proportion of the light that collides with the aerogel increases, so the solar radiation shielding effect becomes greater. In other words, even during the time periods of summer mornings and evenings when the sun's altitude is low, the solar radiation shielding effect can be obtained if the sun's rays hit the window surface at an angle of 60° or more.

[0043] Therefore, it blocks a lot of sunlight during the warm or hot season from April to September, and allows a lot of sunlight to pass through during the cool or cold season from October to March. When such a transparent solar radiation control film is attached to window glass, a transparent solar radiation control film for window glass with good visibility can be obtained, which automatically blocks sunlight in summer and lets in sunlight in winter.

[0044] Hereinafter, preferred embodiments of the transparent solar radiation control film for window glass of the present invention will be described with reference to the accompanying drawings. However, the transparent solar radiation control film for window glass of the present invention is not limited to these embodiments.

[0045] A cross-sectional view of a transparent solar radiation control film for windows according to a preferred embodiment of the present invention is shown in Figure 1. The transparent solar radiation control film for windows 10 has a base film 1 and a transparent solar radiation control adhesive layer 4 in which a silica-shelled aerogel 3 is dispersed in an adhesive 2, and further has a hard coat layer 5 on the opposite side of the transparent solar radiation control adhesive layer 4 with the base film 1 sandwiched therebetween, with each layer laminated in this order. The base film 1 and the window glass surface can be adhered to each other via the transparent solar radiation control adhesive layer 4.

[0046] Fig. 2 shows a cross-sectional view of a transparent solar radiation control film for windows according to another preferred embodiment of the present invention. The transparent solar radiation control film for windows 20 has a base film 11, a transparent solar radiation control resin layer 14 in which silica-shelled aerogel 13 is dispersed in a transparent resin 12, and a hard coat layer 15, and further has an adhesive layer 16 on the opposite side of the transparent solar radiation control resin layer 14 and the hard coat layer 15 with the base film 11 sandwiched therebetween, with each layer laminated in this order. The base film 11 and the window glass surface can be adhered to each other via the adhesive layer 16.

[0047] FIG. 3 shows a schematic diagram of sunlight passing through the silica-shelled aerogel, and FIG. 4 shows a schematic diagram of sunlight passing through the transparent solar radiation control film for windows of the present invention. First, sunlight is irradiated from the sun toward the window glass. The window glass and the adhesive transmit a large amount of sunlight (wavelength 0.3 μm to 3.0 μm). The sunlight that passes through the window glass surface also passes through the adhesive and reaches the outer surface of the partition wall 31 of the silica-shelled aerogel. The sunlight that passes through the adhesive and reaches the silica-shelled aerogel is partially reflected due to the difference in refractive index at the interface between the outer surface of the partition wall 31 of the aerogel and the adhesive, and the rest is transmitted. The sunlight that passes through the silica shell reaches the air layer inside the silica-shelled aerogel. The sunlight that enters the air layer inside the silica-shelled aerogel is partially reflected due to the difference in refractive index at the interface between the inner surface of the partition wall 31 of the silica-shelled aerogel and the internal air layer, and the rest is transmitted. The sunlight that has passed through the internal air layer reaches the inner surface of the silica-shelled aerogel partition wall 32. At the interface between the internal air layer and the inner surface of the silica-shelled aerogel partition wall 32, a portion of the sunlight is reflected and the remainder is transmitted due to the difference in refractive index. The sunlight that has passed through the silica-shelled aerogel partition wall 32 reaches the outer surface of the silica-shelled aerogel partition wall 32. The sunlight that has passed through the silica-shelled aerogel to reach the adhesive is partially reflected and the remainder is transmitted due to the difference in refractive index at the interface with the adhesive at the outer surface of the silica-shelled aerogel partition wall 32.

[0048] Figure 5 shows a schematic diagram of the relationship between the incidence angle of the sun's rays and the number of collisions with the silica-shelled aerogel. In the figure, the incidence angle is indicated by θ. It can be seen that the larger the incidence angle of the sun's rays, the more times they collide with the silica-shelled aerogel 3, and the greater the shielding effect.

[0049] In this way, it is believed that sunlight that has been repeatedly reflected and transmitted is partially reflected and emitted to the outside air, and partially absorbed by the adhesive 2 and emitted to the room or the outside air. In addition, the porous silica-shelled aerogel, whose internal space is partitioned into a range of 5 nm to 100 nm, has a structure in which hollow internal spaces exist continuously, and reflection and transmission can occur continuously at the interface between the inner surface of the partition wall 31 of the silica-shelled aerogel and the internal air layer due to the air layer and the silica shell having a large difference in refractive index, and reflection and transmission can occur continuously at the interface between the internal air layer and the inner surface of the partition wall 32 of the silica-shelled aerogel.

[0050] Next, the solar transmittance as a function of the incidence angle will be described. According to the Beer-Lambert law, the thicker the layer, the lower the transmittance. The layer thickness, and therefore the transmission distance of the sun's rays, can be expressed by the following formula: X=1 / cosθ X = distance traveled by the sun's rays 1 = thickness of the layer θ = angle of incidence

[0051] Conventional hollow particles such as silica shells are required to reduce the bulk density of the silica shells in order to obtain extremely low thermal conductivity, and therefore, aerogels of silica shells, which are made of only the silica shells but not the micropores, and have a very low density, are dispersed in resin to create heat insulating films. For example, the heat insulating film described in Patent Document 4 is an example of a heat insulating film coated with hollow particles with low thermal conductivity, but as mentioned above, with the conventional thickness of the dispersion layer, which is about several μm, it is difficult to obtain a large solar radiation shielding effect no matter how much the thermal conductivity is reduced.

[0052] Solar radiation, i.e., sunlight, has a wavelength of 0.3 μm to 3.0 μm, and by reflecting or absorbing wavelengths in this range, a sunlight shielding effect can be obtained even with a thinner film, so it is preferable to make the silica shell larger than the wavelength of sunlight, 0.3 μm to 3.0 μm. By making the silica shell larger than the wavelength of sunlight, 0.3 μm to 3.0 μm, it is possible to better reflect the silica shell from the surface and interface of the aerogel.

[0053] In order to obtain a solar radiation control effect by reflection, it is preferable to use a silica shell aerogel of the present invention, whose internal space is approximately uniformly divided and whose wavelength is slightly larger than the solar radiation wavelength of 0.3 μm to 3.0 μm. The silica shell aerogel of the present invention is a product obtained by pulverizing the manufactured product into a powder form, and has a complex shape, being an ellipsoid with a long axis, a middle axis, and a short axis, all of which have different distances. Therefore, when the adhesive in which the silica shell aerogel of the present invention is dispersed is coated on a film, the dispersed aerogel tends to collapse inside the adhesive, with the short axis perpendicular to the film substrate and the middle axis and long axis horizontal, which means that the surface area facing sunlight becomes larger and more sunlight can be reflected. Therefore, the distances of the long axis, middle axis, and short axis of one aerogel are measured, and the average value calculated from them is expressed as the "average distance of the long axis, middle axis, and short axis", which is used as an index representing the size of the aerogel. The "average value of the long, median, and short axis distances of silica-shelled aerogels" shown below refers to the average value of the "average value of the long, median, and short axis distances of silica-shelled aerogels" obtained in this manner, and specifically refers to the average value calculated from the average distances of the long, median, and short axes of aerogels randomly selected from 30 points on images taken with a microscope (Keyence Corporation: model number VHX-2000). The average value of the average distance between the major axis, the central axis, and the minor axis of the aerogel is preferably 0.2 μm to 20 μm, more preferably 0.3 μm to 10 μm, and most preferably 0.3 μm to 5 μm. If the average value of the average distance between the major axis, the central axis, and the minor axis of the aerogel is 3 μm or more, the solar radiation control effect of the present invention can be obtained, and if it is 10 μm or less, high visibility and transparency can be maintained.

[0054] In addition, it is preferable to use a silica shell aerogel of the present invention in which the average distances of the long axis, center axis, and short axis are within a certain range. If the range of the average distances of the long axis, center axis, and short axis of the silica shell aerogel of the present invention is 0.2 μm to 20 μm, the wavelength of sunlight can be effectively blocked, and further, it is easy to disperse in the solar radiation control adhesive layer, and the thickness of the solar radiation control adhesive layer can be reduced. Note that the above-mentioned "range of the average distances of the long axis, center axis, and short axis of the silica shell aerogel" refers to the range of average distances effective for blocking sunlight.

[0055] <Film substrate> The substrate film used in the transparent solar radiation control film for windows of the present invention is not particularly limited as long as it transmits visible and near infrared rays and has the strength required for application to a window surface. The material constituting the substrate film is not particularly limited, and may be, for example, a polyester film, a polycarbonate film, a polyacrylic film, etc. Among these, polyester films such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polyarylate are preferred in terms of versatility, visibility, and transparency.

[0056] The thickness of the substrate film is not particularly limited as long as the transparent solar radiation control film for windows has sufficient strength, but is preferably 10 to 200 μm, and more preferably 20 to 150 μm. If the thickness of the substrate film is 10 μm or more, the transparent solar radiation control film for windows can have sufficient strength, and if it is 200 μm or less, high visibility and transparency can be maintained even when the film is attached to glass or the like, and the film can be easily attached to window glass.

[0057] The substrate film may have one or more transparent near-infrared shielding layers.

[0058] <Solar control layer> The solar radiation control layer used in the transparent solar radiation control film for windows of the present invention includes a transparent solar radiation control adhesive layer in which a silica shell aerogel is dispersed in a transparent adhesive layer, or a transparent solar radiation control resin layer in which a silica shell aerogel is dispersed in a transparent resin layer, and these may be formed on one side or both sides of the film for window glass. The transparent solar radiation control resin layer may be formed between the transparent solar radiation control adhesive layer and the film for window glass, or may be formed on the side opposite to the transparent solar radiation control adhesive layer. The solar radiation control layer may be a single layer, or may be a multilayer if necessary. The thickness of the solar radiation control layer was measured using a constant pressure thickness meter (manufactured by Techclock Corporation, model number: PG-02A, minimum display (mm) 0.001).

[0059] The thickness of the solar radiation control layer of the present invention is preferably 10 to 150 μm, more preferably 20 to 100 μm, and most preferably 25 to 50 μm. If the thickness of the solar radiation control layer is 10 μm or more, the adhesive strength with glass or the like can be ensured while maintaining the solar radiation control effect of the present invention, and if it is 150 μm or less, high visibility and transparency can be maintained.

[0060] The solar radiation control layer of the present invention contains 0.02 mass% or more of silica-shelled aerogel based on the total solid content of the solar radiation control layer excluding the silica-shelled aerogel. By containing 0.02 mass% or more of silica-shelled aerogel based on the total solid content of the solar radiation control layer excluding the silica-shelled aerogel, the solar radiation control effect of the present invention can be obtained. In addition, it is preferable that the content of silica-shelled aerogel is 0.02 mass% to 6.0 mass% based on the total solid content of the solar radiation control layer excluding the silica-shelled aerogel. If the content of silica-shelled aerogel is 6.0 mass% or less based on the total solid content of the solar radiation control layer excluding the silica-shelled aerogel, high visibility and transparency can be maintained.

[0061] <Transparent solar radiation control adhesive layer and adhesive> The adhesive used to form the transparent solar radiation control adhesive layer used in the transparent solar radiation control film for windows of the present invention is not particularly limited in type as long as it is transparent and transmits sunlight, and can adhere the transparent solar radiation control film for windows to a window surface. For example, any adhesive such as an acrylic adhesive, a urethane adhesive, or a silicone adhesive can be used, but considering the dispersibility of the silica shell aerogel, an acrylic adhesive is particularly preferably used.

[0062] The pressure-sensitive adhesive may be used alone or in combination of two or more kinds, and other components such as, for example, a tackifier, an ultraviolet absorber, an infrared shielding agent, a plasticizer, a photopolymerizable compound, a photoinitiator, a foaming agent, a polymerization inhibitor, an antiaging agent, a filler, a coupling agent, an antistatic agent, etc. may be added within a range that does not impair the object of the present invention. Note that the ultraviolet absorber, the infrared shielding agent, etc. may be contained in a transparent resin to form an ultraviolet absorber layer, an infrared shielding agent layer, etc. on the surface opposite the pressure-sensitive adhesive or between the pressure-sensitive adhesive and the film surface.

[0063] As described above, the thickness of the transparent solar radiation control adhesive layer is preferably 10 to 150 μm, more preferably 20 to 100 μm, and most preferably 25 to 50 μm. If the thickness of the transparent solar radiation control adhesive layer is 10 μm or more, the adhesive strength with glass or the like can be secured while maintaining the solar radiation control effect of the present invention, and if it is 150 μm or less, high visibility and transparency can be maintained.

[0064] As described above, the transparent solar radiation control adhesive layer contains 0.02 mass% or more of silica shell aerogel based on the total solid content of the transparent solar radiation control adhesive layer excluding the silica shell aerogel. By containing 0.02 mass% or more of silica shell aerogel based on the total solid content of the transparent heat insulating adhesive layer excluding the silica shell aerogel, the solar radiation control effect of the present invention can be obtained. In addition, it is preferable that the transparent solar radiation control adhesive layer contains 0.02 mass% to 6.0 mass% of silica shell aerogel based on the total solid content of the transparent solar radiation control adhesive layer excluding the silica shell aerogel. If the content of silica shell aerogel is 6.0 mass% or less based on the total solid content of the transparent solar radiation control adhesive layer excluding the silica shell aerogel, high visibility and transparency can be maintained.

[0065] <Transparent solar radiation control resin layer and transparent resin> The transparent resin of the transparent solar radiation control resin layer used in the transparent solar radiation control film for windows of the present invention is not particularly limited in type as long as it is transparent and transmits sunlight, and can be adhered to the substrate film surface. For example, any resin such as acrylic resin, urethane resin, silicone resin, etc. can be used, but considering the dispersibility of the silica shell aerogel, acrylic resin is particularly preferably used.

[0066] The transparent resin may be used alone or in combination of two or more kinds. In addition, other components such as an ultraviolet absorber, an infrared shielding agent, a plasticizer, a photopolymerizable compound, a photoinitiator, a foaming agent, a polymerization inhibitor, an antiaging agent, a filler, a coupling agent, and an antistatic agent may be added within a range that does not impair the object of the present invention.

[0067] As described above, the thickness of the transparent solar radiation control resin layer is preferably 10 to 150 μm, more preferably 20 to 100 μm, and most preferably 25 to 50 μm. If the thickness of the transparent solar radiation control resin layer is 10 μm or more, the adhesive strength with glass or the like can be secured while maintaining the solar radiation control effect of the present invention, and if it is 150 μm or less, high visibility and transparency can be maintained.

[0068] As described above, the transparent solar radiation control resin layer contains 0.02 mass% or more of silica-shelled aerogel based on the total solid content of the transparent solar radiation control resin layer excluding the silica-shelled aerogel. By containing 0.02 mass% or more of silica-shelled aerogel based on the total solid content of the transparent solar radiation control resin layer excluding the silica-shelled aerogel, the solar radiation control effect of the present invention can be obtained. In addition, it is preferable that the transparent solar radiation control resin layer contains 0.02 mass% to 6.0 mass% of silica-shelled aerogel based on the total solid content of the transparent solar radiation control resin layer excluding the silica-shelled aerogel. If the content of silica-shelled aerogel is 6.0 mass% or less based on the total solid content of the transparent solar radiation control resin layer excluding the silica-shelled aerogel, high visibility and transparency can be maintained. EXAMPLES

[0069] Example 1 Silica-shelled aerogel "TR-W20" manufactured by Luoyang Tongrun Info Technology Co. Ltd. was dispersed in the adhesive "SK Dyne" manufactured by Soken Chemical & Engineering Co., Ltd. at 0.05 mass%, 0.5 mass%, 1.5 mass%, 3.0 mass%, 5.0 mass%, 7.0 mass%, and 10.0 mass% of the solid content. The silica-shelled aerogel "TR-W20" is made of silica with a refractive index of approximately 1.46 (632.8 nm), has the average value of the average distance between the long axis, middle axis, and short axis of 4.2 μm, has a thermal conductivity of approximately 0.02 W / m·K, and the internal space is partitioned into a range of 5 nm to 100 nm. The above-mentioned "average value of the average distances of the long axis, median axis, and short axis of silica-shelled aerogel" refers to the average value of "the average distances of the long axis, median axis, and short axis of silica-shelled aerogel" calculated from the measured distances of the long axis, median axis, and short axis of one aerogel, as described above. Specifically, it refers to the average value calculated from the average distances of the long axis, median axis, and short axis of 30 aerogels randomly selected from images taken with a microscope (Keyence Corporation: Model No. VHX-2000).

[0070] The above-mentioned silica-shelled aerogel-dispersed adhesive was laminated to a thickness of 35 μm on a polyethylene terephthalate film substrate (hereinafter referred to as PET film) having a size of 5 cm×5 cm and a thickness of 50 μm.Then, a sample was prepared by bonding the PET film having the above-mentioned silica-shelled aerogel-dispersed adhesive laminated to a thickness of 3 mm on a 5 cm×5 cm glass plate as follows. (1) A single sheet of glass 3 mm thick (2) A 3 mm thick plate glass to which a PET film containing 0.05% by mass of silica-shelled aerogel with an average major axis, middle axis, and minor axis distance of 4.2 μm was attached. (3) A 3 mm thick plate glass to which a PET film containing 0.5% by mass of silica-shelled aerogel with an average major axis, middle axis, and minor axis distance of 4.2 μm was attached. (4) A 3 mm thick plate glass to which a PET film containing 1.5% by mass of silica-shelled aerogel with an average major axis, middle axis, and minor axis distance of 4.2 μm was attached. (5) A 3 mm thick glass plate attached with a PET film containing 3.0 mass% silica-shelled aerogel with an average major axis, middle axis, and minor axis distance of 4.2 μm. (6) A 3 mm thick plate glass to which a PET film containing 5.0 mass% of silica-shelled aerogel with an average major axis, middle axis, and minor axis distance of 4.2 μm is attached. (7) A 3 mm thick plate glass to which a PET film containing 7.0 mass% of silica-shelled aerogel with an average major axis, middle axis, and minor axis distance of 4.2 μm is attached. (8) A 3 mm thick plate glass to which a PET film containing 10.0 mass% silica-shelled aerogel with an average major axis, middle axis, and minor axis distance of 4.2 μm is attached.

[0071] The samples (1) to (7) thus obtained were subjected to the following evaluations. The results are shown in Table 1.

[0072] (Visible light transmittance and solar transmittance) The visible light transmittance and solar radiation transmittance were measured using a measuring device SolidSpec-3700DUV (double beam type) manufactured by Shimadzu Corporation, with the incident light angle of 45 degrees and linear polarization. The visible light transmittance was measured at an incident angle of 5°, and the solar radiation transmittance was measured at incident angles of 5°, 30°, 45°, and 60°. Visible light was measured at 380nm to 780nm, and solar radiation was measured at 350nm to 2100nm. In addition, "5°-T" in Table 1 means "incident angle of 5°".

[0073] (Visibility) In addition, as visibility, the haze value at that time was determined according to JIS K7136 using a spectroscopic haze meter (SH7000) manufactured by Nippon Denshoku Industries Co., Ltd. The results are shown in Table 1. Haze value calculation formula: H=Td / Tt×100 H: Haze (%) Td: Diffuse light transmittance (%) Tt: Total light transmittance (%)

[0074] [Table 1]

[0075] When a 50μm thick PET film with silica shell aerogel dispersed in it was attached to a 3mm thick plate glass and the solar transmittance was measured, the relative solar transmittance of the glass alone was taken as 100%, and it was found to have a solar control effect depending on the incident angle: 8.3% at an incident angle of 5°, 9.3% at an incident angle of 30°, 12.2% at an incident angle of 45°, and 19.5% at an incident angle of 60°. Similarly, it was found that other films with different aerogel dispersion rates also have a solar control effect. It can also be seen that if the dispersion amount of silica shell aerogel is 0.05% by mass to 6.0% by mass, the haze value can be kept low, and high visible light transmittance, high visibility, and transparency can be maintained.

[0076] Example 2 The silica shell aerogel "TR-W20" manufactured by Luoyang Tongrun Info Technology Co. Ltd., whose internal space is divided into 5 nm to 100 nm and whose thermal conductivity is 0.2 W / m K, was sieved to classify the aerogel into sizes of 0.2 μm, 2.7 μm, 4.2 μm, 5.1 μm, 15.5 μm, and 15.5 μm for the average distances of the long, middle, and short axes, and each was dispersed at 1.5 mass% in the solid content of the adhesive "SK-Dyne" manufactured by Soken Chemical & Engineering Co., Ltd.

[0077] The above-mentioned silica-shelled aerogel-dispersed adhesive was laminated to a thickness of 35 μm on a PET film measuring 5 cm×5 cm and 50 μm in thickness.Then, the PET film on which the above-mentioned silica-shelled aerogel-dispersed adhesive was laminated to a thickness of 3 mm on a 5 cm×5 cm glass plate was bonded to a thickness of 3 mm in thickness as follows to prepare a sample. (1) 3 mm thick plate glass (also listed in Table 1) (9) A 3 mm thick plate glass to which a PET film coated with an adhesive containing 1.5% by mass of silica-shelled aerogel with an average major axis, middle axis, and minor axis distance of 0.2 μm has been attached. (10) A 3 mm thick plate glass to which a PET film coated with an adhesive containing 1.5% by mass of silica shell aerogel with an average major axis, middle axis, and minor axis distance of 2.7 μm has been attached. (4) A 3 mm thick plate glass to which was attached a PET film coated with an adhesive containing 1.5% by mass of silica-shelled aerogel with an average long axis, middle axis, and short axis distance of 4.2 μm (also listed in Table 1). (11) A 3 mm thick plate glass to which a PET film coated with an adhesive containing 1.5 mass% silica shell aerogel with an average major axis, middle axis, and minor axis distance of 5.1 μm has been attached. (12) A 3 mm thick plate glass to which a PET film coated with an adhesive containing 1.5% by mass of silica-shelled aerogel with an average major axis, middle axis, and minor axis distance of 15.5 μm has been attached. (13) A 3 mm thick plate glass to which a PET film coated with an adhesive containing 1.5% by mass of silica shell aerogel with an average major axis, middle axis, and minor axis distance of 21.4 μm has been attached.

[0078] The thus obtained samples (1), (4) and (9) to (13) were evaluated for (visible light transmittance and solar radiation transmittance) and (visibility) as described in (Example 1). The results are shown in Table 2.

[0079] [Table 2]

[0080] A silica shell aerogel with an average long axis, middle axis, and short axis distance of 0.2 μm to 21.4 μm was dispersed in an adhesive at 1.5 mass%, and a 50 μm thick PET film coated with the aerogel was attached to a 3 mm thick glass plate to measure the visible light transmittance and solar transmittance. When the average long axis, middle axis, and short axis distance of the aerogel was 0.2 μm, the solar transmittance was reduced by 4.7% at an incident angle of 5°, 6.8% at an incident angle of 30°, 8.2% at an incident angle of 45°, and 11.7% at an incident angle of 60°, based on relative values ​​relative to the solar transmittance of the glass alone, which is 100%, indicating that the solar light control effect is due to the incident angle. Similarly, it can be seen that other films with different average values ​​of the average distance of the long axis, middle axis, and short axis of the aerogel also have a solar light control effect.

[0081] If the average value of the average distances of the long axis, center axis, and short axis of the silica shell aerogel is 0.2 μm to 20 μm, the visible light transmittance is high, and high visibility, transparency, and a low haze value can be maintained. The average value of the average distances of the long axis, center axis, and short axis of the silica shell aerogel is preferably 0.2 μm to 20 μm, more preferably 0.3 μm to 10 μm, and most preferably 0.3 μm to 5 μm.

[0082] Example 3 We prepared a silica shell aerogel "TR-W20" manufactured by Luoyang Tongrun Info Technology Co. Ltd., which has an average distance of 0.7 μm between the long, middle and short axes, with the internal space divided into 5 nm to 100 nm, and has a thermal conductivity of 0.02 W / m K. We dispersed this aerogel at 1.5 mass% in the solid content of the adhesive "SK Dyne" manufactured by Soken Chemical & Engineering Co., Ltd.

[0083] The adhesive in which the silica-shelled aerogel was dispersed was laminated to a thickness of 25 μm, 35 μm, 45 μm, 70 μm, 100 μm, and 200 μm on a PET film measuring 5 cm x 5 cm and 50 μm in thickness.Then, samples were prepared by bonding the PET film in which the adhesive in which the silica-shelled aerogel was dispersed to each thickness to a plate glass measuring 5 cm x 5 cm and 3 mm in thickness as follows. (1) 3 mm thick plate glass (also listed in Tables 1 and 2) (14) A 25 μm thick adhesive containing 1.5 mass% silica shell aerogel with an average major axis, middle axis, and minor axis distance of 0.7 μm was applied to a 3 mm thick plate glass with the PET film attached. (15) An adhesive containing 1.5% by mass of silica-shelled aerogel with an average major axis, middle axis, and minor axis distance of 0.7 μm was applied to the PET film, which was then applied to a 3 mm-thick plate glass. (16) A 45 μm thick adhesive containing 1.5 mass% silica shell aerogel with an average major axis, middle axis, and minor axis distance of 0.7 μm was applied to a 3 mm thick glass plate with the PET film attached. (17) A 70 μm thick adhesive containing 1.5 mass% silica shell aerogel with an average major axis, middle axis, and minor axis distance of 0.7 μm was applied to a 3 mm thick glass plate with the PET film attached. (18) A 100 μm thick adhesive containing 1.5 mass% silica shell aerogel with an average major axis, middle axis, and minor axis distance of 0.7 μm was applied to a 3 mm thick glass plate with the PET film attached. (19) A 200 μm thick adhesive containing 1.5 mass% silica shell aerogel with an average major axis, middle axis, and minor axis distance of 0.7 μm was applied to a 3 mm thick plate glass with the PET film attached.

[0084] The thus obtained samples (1) and (14) to (19) were evaluated for (visible light transmittance and solar radiation transmittance) and (visibility) as described in (Example 1). The results are shown in Table 3.

[0085] [Table 3]

[0086] A silica shell aerogel with an average long axis, middle axis, and short axis distance of 0.7 μm is dispersed in an adhesive at 1.5 mass%, and a 50 μm thick PET film coated with the adhesive at a thickness of 25 μm to 200 μm is attached to a 3 mm thick plate glass. When the visible light transmittance and solar transmittance are measured, the relative values ​​based on the solar transmittance of the glass alone, which is 100%, are 3.9% at an incident angle of 5°, 4.7% at an incident angle of 30°, 6.2% at an incident angle of 45°, and 7.8% at an incident angle of 60°, indicating that there is a solar light control effect depending on the incident angle. Similarly, it can be seen that other films with different average values ​​of the average distance of the long axis, middle axis, and short axis of the aerogel also have a solar light control effect.

[0087] If the thickness of the transparent solar radiation control resin layer in which the silica shell aerogel is dispersed is 150 μm or less, the visible light transmittance is high, and high visibility, transparency, and a low haze value can be maintained. The thickness of the transparent solar radiation control resin layer in which the silica shell aerogel is dispersed is preferably 10 μm to 150 μm, more preferably 20 to 100 μm, and most preferably 25 to 50 μm.

[0088] As described above, according to the present invention, it is possible to provide a transparent solar radiation control film for windows that exhibits a significant shading effect not only against sunlight incident from above but also against sunlight incident from a low position, has high visibility, is inexpensive, and has excellent light control performance that is not affected by the direction of the sunlight. [Explanation of symbols]

[0089] 1. Base film 2. Adhesive 3. Silica-shelled aerogel 4 Transparent solar dimming adhesive layer 5 Hard Coat Layer 10. Transparent solar control film for windows 11 Base film 12 Transparent resin 13. Silica-shelled aerogel 14 Transparent solar dimming adhesive layer 15 Hard coat layer 16 Adhesive layer 20 Transparent solar control film for windows 30 Silica shell aerogel 31 Bulkhead 32 Bulkhead 33 Air θ angle of incidence

Claims

1. The transparent solar radiation control film for windows is a transparent solar radiation control film for bonding to a window glass substrate, characterized in that the transparent solar radiation control film for windows is formed with a solar radiation control layer on at least one side of a substrate film that transmits sunlight, the solar radiation control layer having a dispersed silica shell aerogel whose internal space is partitioned into a range of 5 nm to 100 nm, and the silica shell aerogel is dispersed in an amount of 0.02 mass % to 6.0 mass % relative to the total solid content of the solar radiation control layer excluding the silica shell aerogel.

2. 2. The transparent solar radiation control film for windows according to claim 1, wherein the average distance between the major axis, the middle axis and the minor axis of the silica shell aerogel is 0.2 μm to 20 μm.

3. The transparent solar radiation control film for windows according to claim 1, wherein the silica shell aerogel is dispersed in an amount of 0.2% by mass to 6.0% by mass relative to the total solid content of the solar radiation control layer excluding the silica shell aerogel.

4. 2. The transparent solar radiation control film for windows according to claim 1, wherein the solar radiation control layer has a thickness of 10 to 150 μm.

5. A method for improving light control performance using the transparent solar radiation control film for windows according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • JP1979093150A

  • Ac motor for car

    JP1981056147A

  • Electric discharge lamp

    JP1983010361A

  • Panel with crime prevention performance and lighting control performance

    JP2020095276A